2018
DOI: 10.1182/blood-2018-99-111418
|View full text |Cite
|
Sign up to set email alerts
|

Elderly AML: A Five-Year Retrospective Review on Prognostic Features

Abstract: Background: Acute Myeloid Leukemia (AML) is a disease of the elderly with a median age of diagnosis of 70 years. Prognosis in this age group is poor, with median overall survival of those undergoing treatment ranging from seven to twelve months. Treatment is difficult for a variety of reasons, including - higher incidence of co-morbid conditions (including frailty and decline in functional status), decreased ability to tolerate infections, socioeconomic considerations, and more aggressive diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…A notable phase 4 study conducted in patients with septic DIC provided results worth considering. This study found no improvement in 28-day mortality associated with the use of antithrombin in this population [128,131,137,[140][141][142][143][145][146][147]. Interestingly, there is growing interest in the concept of combination therapy.…”
Section: Antithrombin and Combination Therapymentioning
confidence: 98%
See 1 more Smart Citation
“…A notable phase 4 study conducted in patients with septic DIC provided results worth considering. This study found no improvement in 28-day mortality associated with the use of antithrombin in this population [128,131,137,[140][141][142][143][145][146][147]. Interestingly, there is growing interest in the concept of combination therapy.…”
Section: Antithrombin and Combination Therapymentioning
confidence: 98%
“…Therefore, the question of whether anticoagulant therapy is generally beneficial for sepsis patients remains a controversial topic in the scientific community. Anticoagulation plays a central role in the body's innate defense mechanisms against infections [139,140]. However, widespread, and indiscriminate use is discouraged due to the increased risk of bleeding.…”
Section: Study Hypothesis Significance and Unanswered Questionsmentioning
confidence: 99%
“…If they form in the wrong places, they can block arteries and prevent blood from reaching organs such as the heart, brain, or lungs, resulting in strokes, heart attacks, pulmonary embolism, or deep vein thrombosis. However, the clotting of blood is necessary for the halting of bleeding . Anticoagulant drugs are generally recommended when one of the aforementioned situations is developed in our body.…”
Section: Fluorescence-driven Sensing Of Various Pharmaceutical Drugs ...mentioning
confidence: 99%
“…Anticoagulants function by stopping the process that results in blood clots. However, the excess use of anticoagulants can result in chest pain, back pain, heavy periods in the case of women and secretion of blood with urine, vomit, and stool. , As a result, measuring the concentration of these medications in various body fluids is required. Several anticoagulant drug sensors have been reported in recent times, and few of them are using fluorescent MOFs.…”
Section: Fluorescence-driven Sensing Of Various Pharmaceutical Drugs ...mentioning
confidence: 99%
“…[3][4][5] These drugs are either used orally (mostly for long-term therapy) or Parenterally (for the prevention and initiation of treatment of thrombosis as well as other surgical procedures) and are among the most frequently implicated medications that cause ADRs in hospitalized patients, mostly elderly patients are at high risk to suffer from anticoagulant-associated ADRs such as ecchymosis, epistaxis, hematuria, gastro intestinal (GI) bleeding, thrombocytopenia, osteoporosis on long term use and hypersensitivity reactions. [6][7][8][9] The present study was aim to evaluate and understand the drug use pattern of oral and Injectable anticoagulants. This prospective study will be helpful to improve current prescription patterns and give insights to minimize the drug therapy problems associated with anticoagulant therapy.…”
Section: Introductionmentioning
confidence: 99%